2011
DOI: 10.1093/infdis/jir724
|View full text |Cite
|
Sign up to set email alerts
|

A Simplified Intravenous Artesunate Regimen for Severe Malaria

Abstract: NCT00522132.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 14 publications
3
40
0
Order By: Relevance
“…Thus, after several years of extensive use of artesunate plus amodiaquine and of artemether plus lumefantrine as first-line treatments for P. falciparum malaria in Niger, there is no evidence of a decline in sensitivity to artemisinin. Our data are similar to those reported in Senegal and Congo and are consistent with findings of studies indicating a lack of decrease in sensitivity to artesunate in Gabon, Senegal, and Djibouti despite the extensive and growing use of ACT in these regions (12)(13)(14)(15)(16)(17)(18). A decrease in parasite susceptibility to artemisinin derivatives has been reported to date only in Southeast Asia along the border between Thailand and Cambodia.…”
supporting
confidence: 92%
“…Thus, after several years of extensive use of artesunate plus amodiaquine and of artemether plus lumefantrine as first-line treatments for P. falciparum malaria in Niger, there is no evidence of a decline in sensitivity to artemisinin. Our data are similar to those reported in Senegal and Congo and are consistent with findings of studies indicating a lack of decrease in sensitivity to artesunate in Gabon, Senegal, and Djibouti despite the extensive and growing use of ACT in these regions (12)(13)(14)(15)(16)(17)(18). A decrease in parasite susceptibility to artemisinin derivatives has been reported to date only in Southeast Asia along the border between Thailand and Cambodia.…”
supporting
confidence: 92%
“…Any new medicine would therefore have to free up the microvasculature, either by disengaging or killing the parasites; the drug’s speed of onset of activity is therefore of paramount concern. The AQUAMAT and SEAQUAMAT studies that compared intravenous artesunate and intravenous quinine [74, 75] and other studies that compared intravenous or intramuscular artesunate [76, 77] showed that injected artesunate reduces the overall severe malaria patient mortality by between a third and a quarter. From a safety viewpoint, quinine use has been associated with injection-site pathologies, cinchonism [78, 79] and also risks of hypoglycemia.…”
Section: Severe Malariamentioning
confidence: 99%
“…A CDC evaluation reported no case of haemolysis after the use of intravenous artesunate preparations produced under strict good manufacturing practice (GMP) conditions by the US Army Medical Material Development Activity in 2013, including a study in 197 African children with severe malaria treated with GMPcompliant intravenous artesunate. 25,27 However, Bryan et al subsequently identified one case of artemisinin-associated haemolysis in the USA and two cases in Canada, both following the use of the GMP-compliant drug formulation. 26 Both cases of haemolysis associated with the use of oral artemether-lumefantrine involved a GMP-compliant product from Novartis.…”
Section: Description Of Pharmaceutical Productsmentioning
confidence: 99%